Diversity of Bacterial Phenol Hydroxylase-encoding Genes from Fuel- contaminated Silt Soil - Suraj Rajan Vasandani (Indonesian Society for microbiology, 2023)
Phenol is an aromatic compound often used as a raw material or intermediate in various industries. Improper handling and disposal may lead to the accumulation of this hazardous compound. Bioremediation is the most viable method to remove phenol from contaminated environment. In this study, the diversity of genes that encode for phenol hydroxylase, a key enzyme in phenol degradation, was assessed in gasoline-contaminated soil in a commercial gas station in Central Jakarta, Indonesia. Partial phenol hydroxylase-encoding gene library was constructed using a pair of universal primer in the pGEM-Teasy vector. A total of 30 recombinant clones were obtained and sequenced to analyze the genetic diversity of this gene. Obtained clones were 86–99% identical to phenol hydroxylase-related proteins. Phylogenetic tree analysis on amino acid sequences derived from our library revealed that 56.67% of the cloned fragments were closely related to Proteobacteria, while 20% of the clones were clustered with Actinobacteria. The rest 23.33% of the clones formed a cluster separate from any of the reference sequences, possibly indicating the presence of novel phenol hydroxylase genes.